EFFECT OF KINTEIN AND SALICYLIC ACID ON CARRYFFLOWER (Carthamus tinctorius L.) TOLERENCG WATER-STRESS - & Hamed, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was carried out at the plant garden -Science Dep. of Sciences College of Basic Education, Almustansriyah Univ. the objective was to study the effect of Kinetin and Salicylic acid at two growth stages, using split–split plot design with three replicates .Irrigative treatment (every 3,6,9 weeks) .and main plots , plant regulators (control, Kinetin spray and Salicylic acid spray ) as sub plots, while,growth regulator spray stages(tillring initiation, flowers budinitiation sub-sub plots The results were revealed, The Plants which irrigated every 3 and 6 weeks look longer time from 100% flowering to physiological watering(66.67 , 68.22 days)highest number of heads.plants-1 ( 45 .00 ,38.56 heads.Plant-1.Theplants which irrigated every 6 weeks produced highest seed yield( 3159.17 kg .ha-1) harvest index(51.57%) oil percent(37.63).The plants sprayed salicylic acid produc ed highest, plant highest, biological yield ,water use efficiency .The results were revealed possibility of Kinetin spraying during the vegetative growth and Salicylic acid during fertilization stage , helpstoincrease seed yield and oil percent.